Mental health impact of the COVID-19 pandemic in U.S. military veterans: a population-based, prospective cohort study - Hill, Melanie L. (Psychol Med, 2023)
BACKGROUND: The coronavirus disease-2019 (COVID-19) pandemic has caused myriad health, social, and economic stressors. To date, however, no known study has examined changes in mental health during the pandemic in the U.S. military veteran population. METHODS: Data were analyzed from the 2019–2020 National Health and Resilience in Veterans Study, a nationally representative, prospective cohort survey of 3078 veterans. Pre-to-peri-pandemic changes in psychiatric symptoms were evaluated, as well as pre-pandemic risk and protective factors and pandemic-related correlates of increased psychiatric distress. RESULTS: The prevalence of generalized anxiety disorder (GAD) positive screens increased from pre- to peri-pandemic (7.1% to 9.4%; p < 0.001) and was driven by an increase among veterans aged 45–64 years (8.2% to 13.5%; p < 0.001), but the prevalence of major depressive disorder and posttraumatic stress disorder positive screens remained stable. Using a continuous measure of psychiatric distress, an estimated 13.2% of veterans reported a clinically meaningful pre-to-peri-pandemic increase in distress (mean = 1.1 standard deviation). Veterans with a larger pre-pandemic social network size and secure attachment style were less likely to experience increased distress, whereas veterans reporting more pre-pandemic loneliness were more likely to experience increased distress. Concerns about pandemic-related social losses, mental health COVID-19 effects, and housing stability during the pandemic were associated with increased distress, over-and-above pre-pandemic factors. CONCLUSIONS: Although most U.S. veterans showed resilience to mental health problems nearly 1 year into the pandemic, the prevalence of GAD positive screens increased, particularly among middle-aged veterans, and one of seven veterans experienced increased distress. Clinical implications of these findings are discussed.